2021
DOI: 10.1016/j.copsyc.2020.07.006
|View full text |Cite
|
Sign up to set email alerts
|

A review investigating the relationship between cannabis use and adolescent cognitive functioning

Abstract: Highlights Early age of onset of cannabis use among adolescents is associated with increased likelihood of poor cognitive function and mental health. Persistent cannabis use is associated with decreased academic performance scores. Racial disparities exist among adolescent cannabis users as well as the negative sequalae associated with cannabis use in this group. Adolescents from states with medical marijuana laws were less likely to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Although one cannot interpret null effects, it is possible that lower EF is a risk factor specifically for more frequent cannabis use, rather than infrequent use or “experimentation.” Furthermore, this finding mirrors prior cross-sectional studies that have found lower EF to be related to greater cannabis use frequency in adolescents, young adults, and adults (Block et al, 2022; Castellanos-Ryan et al, 2017; Dahlgren et al, 2016; Gruber et al, 2012; Lahanas & Cservenka, 2019; Lisdahl & Price, 2012). It is worth noting that frequent cannabis use in adolescence and young adulthood have been associated with various negative outcomes, including poorer cognitive functioning (Cyrus et al, 2021; Scott et al, 2018), decreased academic performance (Cyrus et al, 2021), higher levels of other substance use and substance use-related problems (Chan et al, 2021; Foster et al, 2018), and alterations in brain function and development (Blest-Hopley, Colizzi, et al, 2020; Blest-Hopley, Giampietro, et al, 2020). As such, child EF may serve as an important target for interventions aimed at preventing, delaying, or decreasing frequent cannabis use.…”
Section: Discussionmentioning
confidence: 99%
“…Although one cannot interpret null effects, it is possible that lower EF is a risk factor specifically for more frequent cannabis use, rather than infrequent use or “experimentation.” Furthermore, this finding mirrors prior cross-sectional studies that have found lower EF to be related to greater cannabis use frequency in adolescents, young adults, and adults (Block et al, 2022; Castellanos-Ryan et al, 2017; Dahlgren et al, 2016; Gruber et al, 2012; Lahanas & Cservenka, 2019; Lisdahl & Price, 2012). It is worth noting that frequent cannabis use in adolescence and young adulthood have been associated with various negative outcomes, including poorer cognitive functioning (Cyrus et al, 2021; Scott et al, 2018), decreased academic performance (Cyrus et al, 2021), higher levels of other substance use and substance use-related problems (Chan et al, 2021; Foster et al, 2018), and alterations in brain function and development (Blest-Hopley, Colizzi, et al, 2020; Blest-Hopley, Giampietro, et al, 2020). As such, child EF may serve as an important target for interventions aimed at preventing, delaying, or decreasing frequent cannabis use.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, due to more craving in the CUD group, reappraisal strategies may become more difficult. Another reason could be that drug use can interrupt cognitive and executive function ( Cyrus et al, 2021 , Dolcos et al, 2011 , Núñez et al, 2016 ). Therefore, due to these cognitive changes, the use of reappraisal strategies occurs less in the CUD group.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that cannabis (marijuana) accounts for more than half of all drug-related offences globally (UNODC, 2020a). Additionally, cannabis is reported as the most widely consumed psychoactive substance worldwide, especially in developed countries, for medical, recreational (Ajayi & Somefun, 2020; Alasmari, 2013; Cyrus et al, 2020), and other purposes. However, new psychotropic substances (NPS) are reported to be on the rise (UNODC, 2020a).…”
Section: Related Literaturementioning
confidence: 99%